2020
DOI: 10.3389/fmicb.2020.00244
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Solid-, Liquid-, and Epithelium-Associated Bacterial Communities in the Rumen of Hu Lambs in Response to Dietary Urea Supplementation

Abstract: Frontiers in Microbiology | www.frontiersin.org February 2020 | Volume 11 | Article 244 Li et al.Urea Affects Rumen Bacteiral Communities epithelial fraction of the UC and LU treatments relative to HU treatment. Comparisons of predictive function in the rumen solid, liquid, and epithelial fractions among the three treatments also revealed differences. Collectively, these results reveal the change of the rumen bacterial community to dietary urea supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 72 publications
9
28
0
Order By: Relevance
“…In line with previous studies [15,18,26], the RE bacterial diversity was lower than that in the RS or the RL fraction (Table 2), and the bacterial composition was greatly distinct from that of the RS or the RL (Table 3). At the phylum level, contrary to the finding in the RS or the RL, Firmicutes was the first while Bacteroidetes the second largest phyla in the RE microbiota.…”
Section: Differences In Microbiota Between Epithelial and The Solid Osupporting
confidence: 91%
See 4 more Smart Citations
“…In line with previous studies [15,18,26], the RE bacterial diversity was lower than that in the RS or the RL fraction (Table 2), and the bacterial composition was greatly distinct from that of the RS or the RL (Table 3). At the phylum level, contrary to the finding in the RS or the RL, Firmicutes was the first while Bacteroidetes the second largest phyla in the RE microbiota.…”
Section: Differences In Microbiota Between Epithelial and The Solid Osupporting
confidence: 91%
“…Consistent with previous studies using PCR-DGGE [17] or high-throughput sequencing [15,18,26], RS and RL shared more bacteria when compared to RE. In addition, the predicted functions and the qPCR results of the microbial groups further demonstrated that there were great differences in the structure and function of the microbiota occupying different REN.…”
Section: Effects Of Ruminal Ecological Niche On Microbiota Structure supporting
confidence: 91%
See 3 more Smart Citations